Trypanosoma cruzi antigen detection in blood to assess treatment efficacy and cure in mice models of Chagas disease - de Araujo, Fernanda Fortes; Nagarkatti, Rana; Mazzeti, Ana Lia; Gonçalves, Karolina Ribeiro; Figueiredo Diniz, Lívia de; Campos do Vale, Isabela; Martins-Filho, Olindo Assis; Debrabant, Alain; Bahia, Maria Terezinha; Teixeira-Carvalho, Andréa (Frontiers in Immunology, 2024)
Chagas disease (CD) is caused by the protozoan parasite Trypanosoma cruzi. Although endemic mainly in Latin America, CD has become a global public health problem due to migration of infected individuals to non-endemic regions. Despite progress made in drug development, preclinical assays for drug discovery are required to accelerate the development of new drugs with reduced side effects, which are much needed for human treatment. We used a cure model of infected mice treated with Fexinidazole (FZ) to further validate a novel Enzyme Linked Aptamer (ELA) assay that detects parasite biomarkers circulating in the blood of infected animals. The ELA assay showed cure by FZ in ~71% and ~77% of mice infected with the VL-10 and Colombiana strains of T. cruzi, respectively. The ELA assay also revealed superior treatment efficacy of FZ compared to Benznidazole prior to immunosuppression treatment. Our study supports the use of ELA assay as an alternative to traditional serology or blood PCR to assess the efficacy of antichagasic drugs during their preclinical phase of development. Further, the combination of high sensitivity and ease of use make this parasite antigen detection assay an attractive new tool to facilitate the development of much needed new therapies for CD.